Austroteneriffia shiraziensis sp. nov. (Acari: Teneriffiidae) from southwestern Iran, with description of male and immature stages - Khanjani, Mohammad; Yazdanpanah, Shima; Fayaz, Bahman Asali (Zootaxa, 2013)
A new species, Austroteneriffia shiraziensis sp. nov., is described and illustrated from soil under oak trees in the Koohm-are Sorkhi region, Fars province, south western Iran. The description of A. shiraziensis sp. nov. is based on females, males, deutonymphs, and protonymphs. A key to adult females of Austroteneriffia is provided.